A Comparative Study on Turbulence Models for Simulation of Flow Past NACA 0015 Airfoil Using OpenFOAM - Peerakit Kekina (2018)
© The Authors, published by EDP Sciences, 2017. An implementation of C++ language open source code software, OpenFOAM, for simulation of flow past NACA 0015 airfoil was performed to access a suitable turbulence model. Three various turbulence models were selected which comprised of Spalart-Allmaras model, RNG k-ϵ model and Menter SST k-ω model, respectively. The SIMPLE algorithm and Upwind method was used to solve the governing equation to achieve flow solutions of computational fluid dynamic (CFD) models. The flow simulation obtained lift coefficient (CL) and drag coefficient (CD) to compare with the wind tunnel experiment data at Reynolds number (Re) of 160,000 and 360,000 with the large range airfoil angle of attack (AOA) from 0 to 20 degree. The suitable CFD model was the Menter SST k-ω model which obtained an average error of CLand CDless than 10.96% and 22.21%, respectively.